Cultural rights and “Masterpieces” of Local and Translocal Actors: A Study of Italian and Spanish cases - Giguère, Hélène (Ethnologies, 2014)
This paper deals with European experiences of inscription of traditional cultural practices on UNESCO’s Representative List of Intangible Cultural Heritage (ICH). It will first establish the institutional context of the UNESCO’s listing within the framework of reflections on cultural rights. Then, the author briefly presents four European masterpieces in the Mediterranean area. A comparative analysis follows which specifically focuses on the multiplication of practitioners and on translocality; on the overlapping between institutions and artisans; on the use of intangible cultural heritage as a driver for local development via cultural tourism; and on the multimedia “museification” of the intangible. The comparative study of the listing of these intangible cultural heritage traditions also questions the value of customary law versus freedom of expression and creation. It reveals the tensions between the “purity” and “impurity” of cultural practices and social agents, as well as exclusions related to ethnicity, sex or territory. These tensions create new social divisions and remodel the link people have with cultural practices. An examination of gender sheds light on the marginality of women in public space.